“How might this have gone differently if I was not Black?”: Black Mothers Navigating Perinatal Care in the Greater Toronto Area - Bhupaul, Valerie; De Lisio, Amanda (Journal of Critical Race Inquiry, 2025)
Despite documented histories of medical violence against Black women—including harmful interventions, exploitative research, and systemic mistreatment—and the persistent pathologization of Black women in popular narratives of motherhood, there remains a paucity of research on the perinatal experiences of Black women in Canada. This article examines the shared yet distinct perinatal experiences of Black women, drawing on birth stories from the Greater Toronto Area of women who sought care between January 2020 and May 2023. Through their birth stories, we explore the reproduction of race by medical staff, focusing on the stereotype of Black women as inherently resilient and the racial contempt they encounter in perinatal care. Birth stories reveal key strategies that Black women are forced to use to resist obstetric racism and the pathologization of Black motherhood, including prioritizing clear communication, seeking representation among healthcare providers, and choosing midwives as primary caregivers. These experiences provide valuable insights for shaping healthcare policies that centre Black women and birthing people while advancing reproductive justice and dismantling medical violence.